Starlike and Convex Properties for Hypergeometric Functions - Oh Sang Kwon; Nak Eun Cho (International Journal of Mathematics and Mathematical Sciences)
The purpose of the present paper is to give some characterizations for a (Gaussian) hypergeometric function to be in various subclasses of starlike and convex functions. We also consider an integral operator related to the hypergeometric function.